Factors Affecting Female Age at Marriage in Dhankuta - Pokhrel, Shantanu; Parajuli, Kewal Ram (Rupantaran: A Multidisciplinary Journal, 2025)
Being a universal social institution, marriage is generally viewed to represent a very important social achievement in Nepal because its incidence is influenced by multiple socio-economic factors to differing extents. Though there has been a slow shift in the marriage age, child marriage remains prevalent, especially in rural women. It is interlinked with health as well as education and economic dimensions. The current paper attempts to discuss some proximate socioeconomic and cultural factors that shape female age at marriage in Dhankuta Municipality, as a semi-urban area where age-old customs are blending with modern social norms. This study used a descriptive research design based on primary data from 185 evermarried women aged between 15 and 49 years collected through a structured questionnaire. Additional information was gathered from national census records and other secondary published and unpublished sources. The analysis has been carried out based on averages and percentages to trace the pattern and degree of association between some selected variables with the help of cross-tabulation with marital age. A mean age at marriage of 20.05 years has been observed to vary significantly by the education, occupation, and background of the family of women. The findings reveal that women who are literate and have attained higher schooling, and respondents from families where the main occupation is not agriculture, consistently marry later than their counterparts. Other determinants were age at menarche, type of marriage, and family structure where later biological maturity, nuclear household, and nonarranged union have a positive relationship with marital age. It reconfirms that the determinants of female age at marriage comprise an interplay between educational achievements, economic conditions, cultural, and biological factors. Immediate policy interventions include girls’ education, non-agricultural job opportunities as well as awareness campaigns are suggested.